European sovereignty, legitimacy, and power - Szewczyk, Bart M. J. (Abingdon, Oxon ; New York, NY: Routledge, 2021)
"This book shows how the EU's dual sovereignty-legitimacy problem can be resolved through the political concept of European citizenship, which can serve both to define the scope of European sovereignty and to justify EU power beyond national democracy. It reconceptualizes the EU's legitimacy problem and demonstrates how sources of legitimacy can be identified and give rise to European sovereignty. It argues that sovereignty should be based on the will of citizens acting through various political bodies within the EU: city halls, regional entities, national governments, and EU institutions, and develops a general theory, arguably applicable to any political order. The EU is an unprecedented political project that is in tension with traditional forms of state legitimation based on national democracy, as nationalist and populists throughout Europe often make clear. Against this backdrop, the book fully articulates the notion of European sovereignty and argues that the EU's sources of legitimacy are based on European citizenship and national democracy. This book will be of key interest to scholars and students of European Union politics, European integration, international institutions and more broadly to international relations"--
Introduction -- Theories of sovereignty and legitimacy -- Insufficient solutions to the EU's sovereignty-legitimacy problem -- Internal sources of EU principles -- External sources of EU principles -- European citizenship and national democracy -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: European Union; Legitimacy of governments -- European Union countries; Citizenship -- European Union countries; Democracy -- European Union countries; Political participation -- European Union countries